2008
DOI: 10.1002/ptr.2481
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of xanthohumol from hops (Humulus lupulus L.) on human hepatocellular carcinoma cell lines

Abstract: Xanthohumol is one of the main flavonoids in hop extracts and in beer. Very few investigations of xanthohumol have studied hepatocellular carcinoma. In this study, the inhibitory effects of xanthohumol on human hepatocellular carcinoma cell lines were investigated. The IC(50) values of xanthohumol for two hepatocellular carcinoma cell lines and one normal hepatocyte cell line were 108, 166 and 211 microm, respectively. Normal murine hepatocyte cell line had more resistance to xanthohumol than hepatocellular ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 19 publications
6
20
1
Order By: Relevance
“…Similar to our results on normal and cancer brain cells, Ho et al . () found that a normal hepatocyte cell line was less sensitive to XN than two hepatocellular carcinoma cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to our results on normal and cancer brain cells, Ho et al . () found that a normal hepatocyte cell line was less sensitive to XN than two hepatocellular carcinoma cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the preventive effect of flavonoids, quercetin or Acacia nilotica bark extract (ANBE) via oxidant/antioxidant activity was demonstrated on hepatic cancer in rats [83-85]. Recently several other molecules with antioxidative properties were evaluated (for example, Siraitia grosvenorii extract, black tea polyphenols, xanthohumol from hops (Humulus lupulus L.)) [86-88]. Also, butyric acid (BA) being a member of histone deacetylase inhibitors (HDAI) has been proposed as chemiopreventive agent.…”
Section: Antioxidants Role In Hcc Chemopreventionmentioning
confidence: 99%
“…Thus, stimulation of prostate cancer cells with 20 μM XN resulted in an approximately halved viability (4), and XN concentration of 100 μM induced 100% cell death in breast cancer cells (1). Recently, Ho et al reported that XN induced apoptosis in two HCC cell lines in vitro (29). However, in this study considerably higher XN concentrations (>200 μM) were required to induce death of all HCC cells.…”
Section: Discussionmentioning
confidence: 69%
“…Yang et al described loss of viability in approximately 90% of 3T3-L1 cells, a murine adipocyte cell line, after 24 h treatment with 75 μM XN (39). In the (nonmalignant) murine hepatoma cell line AML12 the maximal applied concentration of 225 μM XN (24 h) induced toxicity in approximately 50% of the cells as reported by Ho et al (29). However, to the best of our knowledge, no data have been reported concerning the effect of XN on primary human cells.…”
Section: Discussionmentioning
confidence: 76%